Taʼleemul haq: an authentic compilation on the five fundamentals of islam - Desai, Shabbir Ahmed E. (Azhar Academy Ltd. ; Abdul Naeem for Islamic Book Service London, New Delhi, 2003)
Ta'leemul Haq is a concise guide on the essential practices of Islam, covering the five pillars with practical instructions and authentic references.